Coming Full Circle : Constructing Native Christian Theology - Charleston, Steven, 1949- (Book collections on Project MUSE., 2015)
Coming Full Circle provides a working constructive dogmatics in Native Christian theology. Drawing together leading scholars in the field, this volume seeks to encourage theologians to reconsider the rich possibilities present in the intersection between Native theory and practice and Christian theology and practice. This innovative work begins with a Native American theory for doing constructive Christian theology and illustrates the possibilities with chapters on specific Christian doctrines in a "theology in outline." This volume will make an important contribution representing the Native A.